2020
DOI: 10.1055/s-0040-1712547
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Treatment and Prevention Strategies against COVID-19: A Brief Update

Abstract: Patients with novel coronavirus disease 2019 (COVID-19) are at significantly increased risk for mortality and morbidity. Current management remains supportive care, ranging from symptomatic outpatient management to full–intensive care support, including intravenous fluids, invasive, and non-invasive oxygen supplementation. In patients with septic shock, treatment with antibiotics and vasopressors are recommended to keep mean arterial pressure (MAP) ≥ 65 mm Hg and lactate < 2 mmol/L. Because of the lack of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…The design of a vaccine offering active protective immunity will be the most successful long-term strategy for preventing potential outbreaks of this virus. As of April 2020, 115 vaccine candidates were included in the international COVID-19 vaccine research and design landscape [ 63 ]. The most crucial candidate vaccines include viral vector vaccines, nucleic acid-based vaccines, aAPC vaccines, viral proteins and live vaccines [ 12 , 20 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The design of a vaccine offering active protective immunity will be the most successful long-term strategy for preventing potential outbreaks of this virus. As of April 2020, 115 vaccine candidates were included in the international COVID-19 vaccine research and design landscape [ 63 ]. The most crucial candidate vaccines include viral vector vaccines, nucleic acid-based vaccines, aAPC vaccines, viral proteins and live vaccines [ 12 , 20 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese study involving more than 100 COVID-19 patients found chloroquine superior to the control group to minimize the length of the symptoms, worsen pneumonia including radiological improvement and encourage virus-negative seroconversion without significant side effects. This was the first human trial ever performed against COVID-19 with chloroquine; this early outcome has led China to use chloroquine in COVID-19 prevention and treatment [97]. In the absence of serious side effects, early findings from more than 100 patients participating in studies performed in China demonstrated the superiority of chloroquine relative to control in terms of reduction of pneumonia exacerbation, length of symptoms and delay in viral clearance [98].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…15 Although in the review by Kant Kumar et al, they have comprehensively covered most of the main pipeline drugs, a few more, we believe, are worthy of a mention here. 2 As we said earlier, in this unprecedented time, authors are relaying on the results of their studies through prepublication portal till the paper is peer-reviewed. One of such drug is favipravir which is a RNA polymerase inhibitor drug and it has shown its efficacy against influenza virus and Ebola virus infection.…”
mentioning
confidence: 99%
“…That being said, the review by Kant Kumar et al published in this journal is a welcome manuscript which adequately summarizes the available therapeutic options as of now and briefly touches upon the status of vaccine development. 2 It is very reassuring that majority of patients with COVID-19 disease have a mild course and only approximately 10 to 15% of them require substantial health care facility and specific treatment. 3 Therefore, the mainstay of treatment of COVID-19 is supportive for all the stages of the disease and use of lung protective ventilation, Surviving Sepsis Guidelines for COVID, and investigational agents only in a few selected patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation